2012
DOI: 10.1002/psc.2441
|View full text |Cite
|
Sign up to set email alerts
|

Improved anticancer potency by head‐to‐tail cyclization of short cationic anticancer peptides containing a lipophilic β2,2‐amino acid

Abstract: We have recently reported a series of synthetic anticancer heptapeptides (H-KKWβ(2,2) WKK-NH(2) ) containing a central achiral and lipophilic β(2,2) -amino acid that display low toxicity against non-malignant cells and high proteolytic stability. In the present study, we have further investigated the effects of increasing the rigidity and amphipathicity of two of our lead heptapeptides by preparing a series of seven to five residue cyclic peptides containing the two most promising β(2,2) -amino acid derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Additionally, cyclization of the short human and bovine LF-derived peptides did not change the anti-Jurkat activity of the peptides, even though others have shown that cyclization can promote the antimicrobial and anticancer activities of similar peptides , Wessolowski et al 2004, Nguyen et al 2010, Tørfoss et al 2012). …”
Section: Cytotoxicity Towards Jurkat Cellsmentioning
confidence: 88%
“…Additionally, cyclization of the short human and bovine LF-derived peptides did not change the anti-Jurkat activity of the peptides, even though others have shown that cyclization can promote the antimicrobial and anticancer activities of similar peptides , Wessolowski et al 2004, Nguyen et al 2010, Tørfoss et al 2012). …”
Section: Cytotoxicity Towards Jurkat Cellsmentioning
confidence: 88%
“…There are also some concerns related to the use of AMPs whose sequences are close to human and natural AMPs due to a possible compromise of the human natural defense and consequently threat to public health (Chen et al, 2012). On a positive view, since ACPs are not directed to a specific extracellular or intracellular receptor, some mechanisms of resistance can be impaired (Giuliani et al, 2007; Torfoss et al, 2012b) and actually some AMPs have shown cytotoxic activity against MDR cancer cells (Johnstone et al, 2000). The success for obtaining an optimal ACP relies then on the manipulation of its sequence, net charge, secondary structure, oligomerization ability, amphipathicity and hydrophobicity while maintaining high serum stability.…”
Section: Perspectives and Open Questions On Anticancer Peptides Desigmentioning
confidence: 99%
“…It is therefore expected that other cationic residues might be used when constructing an ACP, such as lysine, to direct the peptide binding toward the negatively charged cells and simultaneously avoid hemolytic events. Serum stability might be improved by the incorporation of D-amino acids on the peptide sequence (Riedl et al, 2011b) and by cyclization of the structures (Torfoss et al, 2012b). The incorporation of lipophilic β 2, 2 amino acids building blocks into heptapeptides resulted in a potent anticancer activity toward human and murine lymphoma cells, as well as high proteolytic stability and low toxicity against non-tumor cells (Torfoss et al, 2012a,b).…”
Section: Perspectives and Open Questions On Anticancer Peptides Desigmentioning
confidence: 99%
See 1 more Smart Citation
“…Tørfoss et al discovered a series of synthetic anticancer heptapeptides (H-KKWβ 2,2 WKK-NH 2 ) containing a central achiral and lipophilic β 2,2 -amino acid, which showed high proteolytic stability but low toxicity against normal cells [53]. They further prepared a series of seven to five residue cyclic peptides containing the two most promising β 2,2 -amino acid derivatives as part of the central lipophilic core and proved that a considerable increase in anticancer potency following head-to-tail peptide cyclization [54].…”
Section: Cyclizationmentioning
confidence: 99%